Impact of Apple’s Brand Equity Towards Purchase Intentions of Gen Z Thomasians on Secondhand Apple Products - De Guzman, Marie; Tabaquin, Kathryn Louise; Dimaunahan, Paula Jane; Dimaculangan, Ernesto (IJOSMAS, 2022)
Motivated by the growing multi-platform market of secondhand consumer electronics in the Philippines, this study aims to examine the relationship between the consumer-based brand equity of Generation Z Thomasians towards the global brand, Apple, and the level of purchase intentions of those consumers towards secondhand Apple products. This is a descriptive correlational study following a quantitative research design. The researcher used mean and standard deviation to determine the consumer-based brand equity of Apple and the level of purchase intentions of consumers towards secondhand Apple products, then used regression analysis to find the correlational relationship. This study found that there is a significant relationship between the said two variables. The data for this study was collected from a sample group of 274 respondents from the University of Santo Tomas. The psychometric measures were validated through Cronbach’s alpha using SPSS. This study contributes to the existing body of brand management and consumer behavior literature. Furthermore, this study is beneficial towards technology brand managers and technology marketing managers with regards to developing and improving their brand image and consumer acquisition through their strategic initiatives.